2013
DOI: 10.1021/es403929b
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium–Carbon Hybrid Sorbent for Removal of Fluoride from Water: Oxalic Acid Mediated Zr(IV) Assembly and Adsorption Mechanism

Abstract: When activated carbon (AC) is modified with zirconium(IV) by impregnation or precipitation, the fluoride adsorption capacity is typically improved. There is significant potential to improve these hybrid sorbent by controlling the impregnation conditions, which determine the assembly and dispersion of the Zr phases on carbon surfaces. Here, commercial activated carbon was modified with Zr(IV) together with oxalic acid (OA) used to maximize the zirconium dispersion and enhance fluoride adsorption. Adsorption exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(96 citation statements)
references
References 47 publications
(89 reference statements)
6
90
0
Order By: Relevance
“…However, the more intense absorption peak at 1188.3 cm −1 in both M2 and M3 but correspondingly weaker in raw AC and M1 can be assigned to the C-O associations as previously proposed by Velazquez-Jimenez et al [38] who worked on the sorption of fluorides from water on zirconium oxalate complexes (ZrO x ) supported on AC. A sharp peak at 1084.6 cm −1 in M2 and M3 can be correlated to the attachment of metal (iron) with the oxygen through -interactions, i.e.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopysupporting
confidence: 69%
See 2 more Smart Citations
“…However, the more intense absorption peak at 1188.3 cm −1 in both M2 and M3 but correspondingly weaker in raw AC and M1 can be assigned to the C-O associations as previously proposed by Velazquez-Jimenez et al [38] who worked on the sorption of fluorides from water on zirconium oxalate complexes (ZrO x ) supported on AC. A sharp peak at 1084.6 cm −1 in M2 and M3 can be correlated to the attachment of metal (iron) with the oxygen through -interactions, i.e.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopysupporting
confidence: 69%
“…(Fe O), on iron modified surfaces which was presumed to be due to iron oxide complexes (see EDX results). In another study, an absorption peak appearing at 1084 cm −1 has been attributed to the Zr O an indication of a metal-oxygen interaction [38]. These observations are in good correlation with the findings of Kong et al [58], who suggested the presence of absorption peaks at 1020 and 820 cm −1 in the spectrum of V 2 O 5 , resulted from the stretching in V-O bond of vanadyl group (V O) and due to the vibrations in vanadium oxide bridge system (V-O-V), respectively.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 92%
See 1 more Smart Citation
“…Peak around 2933 cm −1 is due to the stretching vibration of CH 2 bands. The sharp peak at 1376 cm −1 is attributed to the bending vibration of Zr OH bands [50,51]. After fluoride treatment F-Zr-PAAGCB (Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
“…The Zr 2p spectrum (Fig. 5f) can be fitted into two doublepeak components with binding energies at about 182.3 eV and 183.1 eV, which were assigned to ZrO 2 and zirconium complex respectively [30,43,44]. As seen from the XPS, the main components of the conversion coating are MgF 2 , Mg(OH) 2 , MgO, TiO 2 , ZrO 2 and the Ti and Zr metal-organic complex.…”
Section: Xps Studiesmentioning
confidence: 92%